Technical libraries: their organization and management - Special Libraries Association; Strauss, Lucille Jackson (New York : Special Libraries Association, 1951)
The purpose of this book is to present a description of the function of special libraries in the subject fields of the science and related technologies as represented particularly in the science technology division of the special libraries association.
Includes Bibliographic Index
aia 5/7/17
Loans
Keywords: Science and technology libraries